The focusing and informational effects of norms on pro-social behavior - Erin Krupka; Roberto A. Weber (Institute for the Study of Labor (IZA), 2007)
This paper reports an experiment examining the effect of social norms on pro-social behavior. We test two predictions derived from work in psychology regarding the influence of norms. The first is a focusing influence, whereby norms only impact behavior when an individual's attention is drawn to them; and the second is an informational influence, whereby a norm exerts a stronger impact on an individual the more others he observes behaving consistently with that norm. We find support for both effects. Either thinking about or observing the behavior of others produces increased pro-social behavior even when one expects or observes little pro-social behavior on the part of others and the degree of pro-social behavior is increasing in the actual and expected pro-social behavior of others. This experiment eliminates strategic influences and thus demonstrates a direct effect of norms on behavior.
Keywords: D63; 330; Norms; pro-social behavior; experiments; dictator game; Soziale Norm; Soziales Verhalten; Sozialpsychologie; Information; Test